Certificação de composições de serviços web semânticos - Pessini, Evando Carlos (2014)
This thesis presents a certification method for semantic web services compositions which aims to statically ensure its functional correctness. Certification method encompasses two dimensions of verification, termed base and functional dimensions. Base dimension concerns with the verification of application correctness of the semantic web service in the composition, i.e., to ensure that each service invocation given in the composition comply with its respective service definition. The certification of this dimension exploits the semantic compatibility between the invocation arguments and formal parameters of the semantic web service. Functional dimension aims to ensure that the composition satisfies a given specification expressed in the form of preconditions and postconditions. This dimension is formalized by a Hoare logic based calculus. Partial correctness specifications involving compositions of semantic web services can be derived from the deductive system proposed. Our work is also characterized by exploiting the use of a fragment of description logic, i.e., ALC, to express the partial correctness specifications. In order to operationalize the proposed certification method, we developed a supporting environment for defining the semantic web services compositions as well as to conduct the certification process. The certification method were experimentally evaluated by applying it in three different proof concepts. These proof concepts enabled to broadly evaluate the method certification